Soil organic carbon across varying habitat conditions in the mangrove ecosystem in Sembilang National Park, South Sumatra, Indonesia - FITRI AGUSTRIANI; ISKHAQ ISKANDAR; MUHAMMAD YAZID; TENGKU ZIA ULQODRY; FAUZIYAH FAUZIYAH (Society for Indonesian Biodiversity, 2024)
Abstract. Agustriani F, Iskandar I, Yazid M, Ulqodry TZ, Fauziyah. 2024. Soil organic carbon across varying habitat conditions in the mangrove ecosystem in Sembilang National Park, South Sumatra, Indonesia. Biodiversitas 25: 4603-4612. Mangrove ecosystems play an important role in the global carbon cycle, but the Soil Organic Carbon (SOC) stock in these systems was not well-documented in some areas, including in Sembilang National Park (SNP), South Sumatra Province, Indonesia. This study aimed to estimate the SOC values of the mangrove ecosystem under different habitat conditions/management zones in the SNP area, namely natural mangroves, restored ponds, mudflats, human settlements, and post-fire forests. Soil samples were collected at depth intervals of 0 to 50 cm from the five different habitat conditions. Soil samples were then analyzed using the loss-of-ignition method for estimating the SOC stock. Mangrove density was assessed using the Normalized Difference Vegetation Index (NDVI) method. Statistical analyses of Kruskal-Wallis and Dunn’s post-hoc tests with a significance threshold of 0.05 were used to examine differences in SOC stocks across habitat types. The result showed that the average SOC in the mangrove ecosystem in the SNP area was 177.26±60.20 Mg C ha-1. Natural mangroves had the highest SOC value with 220.98 Mg C ha-1 followed by settlements (174.18 Mg C ha-1), mudflats (160.87 Mg C ha-1), and post-fire forests (156.84 Mg C ha-1), while restored pond had the lowest with 114.07 Mg C ha-1. Significant differences in SOC values were found among habitat conditions according to the Kruskal-Wallis test (p = 0.01<0.05), but only between natural mangroves and restored ponds were statistically significant based on post-hoc analysis (Dunn's, p = 0.01<0.05). This result demonstrated that land use changes (as in the case of ponds) affect SOC in the mangrove ecosystem, implying the importance of conserving the remaining natural mangroves and restoring the degraded mangrove habitats (e.g. pond, post-fire area) in the SNP area. This study suggests that an effort should be considered to integrate soil carbon into green economic plans, especially the mangrove conservation in the Banyuasin coastal wetlands.